Productivity of a Triticale and Crimson Clover Winter Cover Crop for Dairies - K. Olagaray; C. Takiya; M. Scheffel; T. Brown; J. S. Stevenson; D. H. Min; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2017)
The potential for a winter cover crop to align with agronomic objectives and to support milk production was evaluated at the Kansas State University Dairy Teaching and Research Center, Manhattan, KS. August planting of a triticale and crimson clover blend following corn silage harvest resulted in production of more than 3.5 tons of dry matter prior to subsequent corn planting. After ensiling, the impact of triticale/crimson clover silage (TCS) on milk production was evaluated in 48 mid- to late-lactation Holstein cows. Cows were blocked by parity (1 and 2+) and milk production, then randomly assigned within block to treatment sequence and pen. The crossover design consisted of two 21-day periods, with 17 days of diet adaptation and 4 days of sampling. Treatments were a diet which included TCS at 15% of diet dry matter (DM) and a control ration in which TCS was primarily replaced by alfalfa and grass hays. The TCS diet included additional bypass soybean meal in an attempt to balance metabolizable protein supply across diets. Samples of rations, feed refusals, and milk were obtained daily, and milk yield was recorded. The TCS diet decreased dry matter intake (48.4 vs. 55.9 ± 3.4 lb/d; P = 0.02), but did not alter milk yield (P = 0.97); therefore, feed efficiency was greater for the TCS diet (P = 0.04). Milk fat concentration tended to increase on the TCS diet (P<0.10) whereas milk lactose yield tended to be lesser for TCS (P = 0.09), but other milk components analyzed (milk protein, MUN, SCC) did not differ between diets (P>0.15). Utilization of TCS also impacted the dairy’s nutrient management plan, as the winter forage harvest removed 40 and 340 lb/a of phosphorus and potassium, respectively. Overall, the blend of triticale and crimson clover as a winter cover crop produced good quality silage that maintained high milk production while also removing key nutrients from the soil to benefit nutrient management planning.
Keywords: triticale; crimson clover; silage; phosphorus